Pregnancy in women with thalassemia dependent transfusion: A case report on the importance of multidisciplinary surveillance to improve maternal and child safety - Made Oka Heryana; Kris Gratia Ageng Nanda; Pradana Zaky Romadhon; Kartika Prahasanti (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Thalasemia affects hemoglobin production. Transfusion-dependent thalassemia is a demanding clinical condition requiring lifelong care and follow-up. A 38-year-old woman is pregnant with her fourth child at 35 weeks gestation. This woman was diagnosed with Hb-E thalassemia-dependent transfusion (Hb electrophoresis showing Hb E 51.5%, Hb F 41.5%, and Hb A 3.5%). The Patient appeared pale with anemic conjunctiva, white sclera, and abdominal enlargement due to pregnancy. The Patient weighs 42 kg, and her height is 150 cm (BMI 18.67). Laboratory results were microcytic hypochromic anemia with hemoglobin 7.4 g/dL, erythrocytes 3.12 million/mL, mean cell volume (MCV) 74.0 fl, mean cell hemoglobin (MCH) 23.7 pg, mean cell hemoglobin (MCHC) 32 g/dL, and platelets with a platelet count of 133,000/µL. A cesarean method was chosen to terminate the pregnancy. There was no intrapartum and postpartum complication in this Patient. Her baby was 1.860 grams and 47 cm in length. There are no abnormalities found in the neonatal examination. Management of pregnant women with thalassemia requires special attention from preconception, during pregnancy, and toward delivery time. Multidisciplinary involvement such as hematologists and obstetricians is the primary key to the safety of mothers and children.